On the Nest Structure in Two Species of the Genus Leptochilus (Hymenoptera, Vespidae, Eumeninae) - Fateryga, A.V. (Вестник зоологии, 2013)
Two nests of the wasps Leptochilus alpestris (de Saussure, 1855) and Leptochilus regulus (de Saussure, 1855) collected in the Crimea were described. The nest of L. alpestris was found in the empty snail shell of Monacha fruticola under a stone; it contained one cell sealed with plug made of glued gravel bits. The nest of L. regulus was found in 3 mm hole of a reed stem from trap-nest; it contained 9 cells separated with partitions made of gravel and mud. The unusual larval habit was discovered in L. regulus — they moved mud from the plug of the cell to its bottom before cocoon spinning. Distinctions of the studied nests from ones of the other species of the genus Leptochilus de Saussure, 1853 were discussed. Описано два гнезда ос Leptochilus alpestris (de Saussure, 1855) и Leptochilus regulus (de Saussure, 1855), собранных в Крыму. Гнездо L. alpestris обнаружено в пустой раковине улитки Monacha fruticola под камнем; оно содержало одну ячейку, запечатанную пробкой, изготовленной из склеенных мелких камешков. Гнездо L. regulus выявлено в трехмиллиметровом канале стебля тростника в искусственной гнездовой конструкции; оно содержало 9 ячеек, разделённых перегородками, изготовленными из мелких камешков и земли. У личинок L. regulus было обнаружено необычное поведение — перед плетением кокона они перемещали землю, содержащуюся в пробке ячейки, к её дну. Обсуждаются отличия изученных гнёзд от гнёзд других видов рода Leptochilus de Saussure, 1853.